Prognostic factors for neurological outcomes in Korean targeted temperature management recipients with return of spontaneous circulation after out-of-hospital cardiac arrests: A nationwide observational study - Kim, Jae Guk (Medicine (Baltimore), 2020)
Targeted temperature management (TTM) is recommended for comatose patients after out-of-hospital cardiac arrests (OHCAs). Even after successful TTM, several factors could influence the neuroprotective effect of TTM. The aim of this study is to identify prognostic factors associated with good neurological outcomes in TTM recipients. This study used nationwide data during 2012 to 2016 to investigate prognostic factors associated with good neurological outcomes in patients who received TTM after the return of spontaneous circulation (ROSC). Multivariate logistic regression analysis was conducted to analyse the factors that may affect the neurological outcomes in the TTM recipients. The study included 1578 eligible patients, comprising 767 with good and 811 with poor neurological outcomes. Multivariable analyses showed that OHCA in public places (OR, 1.599; 95% CI, 1.100–2.323, P = .014), initial shockable rhythms (OR, 1.721; 95% CI, 1.191–2.486, P = .004), pre-hospital ROSCs (OR, 6.748; 95% CI, 4.703–9.682, P < .001), bystander cardiopulmonary resuscitation (CPR) (OR, 1.715; 95% CI, 1.200–2.450, P = .003), and primary coronary interventions (PCIs) (OR, 2.488; 95% CI, 1.639–3.778, P < .001) were statistically significantly associated with good neurological outcomes. Whereas, increase of age (OR, 0.962; 95% CI, 0.950–0.974, P < .001) and conventional cooling (OR, 0.478; 95% CI, 0.255–0.895, P = .021) were statistically significantly associated with poor neurological outcome. This study suggests that being younger, experiencing OHCA in public places, having initial shockable rhythm, pre-hospital ROSC, and bystander CPR, implementing PCIs and applying intravascular or surface cooling devices compared to conventional cooling method could predict good neurological outcomes in post-cardiac arrest patients who received TTM.